A hybrid distributed mutual exclusion algorithm - Chang, Ye-In (Microprocessing and microprogramming, 1996)
This paper presents a hybrid approach to distributed mutual exclusion in which two algorithms are combined such that one minimizes message traffic and the other minimizes time delay. In a hybrid approach, sites are divided into groups, and two different algorithms are used to resolve local (intra-group) and global (inter-group) conflicts. In this paper, we develop a hybrid distributed mutual exclusion algorithm which uses Singhal's dynamic information structure algorithm [15] as the local algorithm to minimize time delay and Maekawa's algorithm [7] as the global algorithm to minimize message traffic. Compared to Maekawa's algorithm which needs O(√ N) messages, but two time units delay between successive executions of the Critical Section (CS) (where N is the number of sites in the system), the proposed hybrid algorithm can reduce message traffic by 52% and time delay by 29% at the same time.